Geographical variation of body size in sigmodontine rodents depends on both environment and phylogenetic composition of communities. (1st February 2016) - Maestri, Renan; Luza, André Luís; de Barros, Lurdiana Dayse; Hartz, Sandra Maria; Ferrari, Augusto; de Freitas, Thales Renato Ochotorena; Duarte, Leandro D. S.
Abstract: Aim: Body size variation in animal assemblages is a widely addressed pattern in biogeographical studies, and is affected by both environmental gradients and phylogenetic constraints. However, no study has yet explored to what extent the association between body size variation and environmental gradients across broad spatial scales is influenced by the biogeographical distribution of different phylogenetic lineages. In this study, we discriminate the influences of environmental variables and phylogenetic community composition on body size variation in South American sigmodontine rodents. Location: South America. Methods: We computed the mean body mass of sigmodontine species co‐occurring in 1 × 1° cells across South America. For each cell we recorded mean values for three environmental variables. We characterized the phylogenetic composition of sigmodontine assemblages within each cell using phylogenetic fuzzy‐weighting and principal coordinates of phylogenetic structure (PCPS). We then partitioned out the influence of environmental factors and the phylogenetic community composition on mean body size. Results: Mean body size variation was mostly explained by shared influence of phylogenetic community composition (PCPS) and environmental factors (68%), while exclusive influence of PCPS was low (19%), and of environment was even lower (0.47%). Increases in body size were related to increases in annual mean temperature, and the influence of environment on body size was mediated by the distribution of sigmodontine lineages across South America. Main conclusions: Environment alone was not sufficient to explain body size variation in sigmodontine assemblages. Rather, environmental gradients interacted with historical processes to determine body size variation in the Neotropical assemblages. These results have implications for the way we think of body size gradients across species assemblages, because any gradient in a trait may be a result of differences in the biogeographical distribution of lineages across space, which should be considered in an explicit context.